Genomic region associated with pod color variation in pea (Pisum sativum) - Shirasawa, Kenta (G3 (Bethesda), 2021)
Pea (Pisum sativum) was chosen as the research material by Gregor Mendel to discover the laws of inheritance. Out of seven traits studied by Mendel, genes controlling three traits including pod shape, pod color, and flower position have not been identified to date. With the aim of identifying the genomic region controlling pod color, we determined the genome sequence of a pea line with yellow pods. Genome sequence reads obtained using a Nanopore sequencing technology were assembled into 117,981 contigs (3.3 Gb), with an N50 value of 51.2 kb. A total of 531,242 potential protein-coding genes were predicted, of which 519,349 (2.8 Gb) were located within repetitive sequences (2.8 Gb). The assembled sequences were ordered using a reference as a guide to build pseudomolecules. Subsequent genetic and association analyses led to the identification of a genomic region that controls pea pod color. DNA sequences at this genomic location and transcriptome profiles of green and yellow pod lines were analyzed, and genes encoding 3' exoribonucleases were selected as potential candidates controlling pod color. The results presented in this study are expected to accelerate pan-genome studies in pea and facilitate the identification of the gene controlling one of the traits studied by Mendel.